Nuclear Transmutation of Long-Lived Fission Product I-129 in Radial Blanket of Sodium-Cooled Fast Reactor - Peng, Hong Liem; Donny, Hartanto; Yoshihisa, Tahara; Naoyuki, Takaki (Nuclear Science and Technology, 2019)
An investigation on the nuclear transmutation of elemental long-lived fission product (LLFP) in a fast reactor is being conducted focusing on the I-129 LLFP (half-life 15.7 million years) to reduce the environmental burden. The LLFP assembly is loaded into the radial blanket region of a Japanese MONJU class sodium-cooled fast reactor (710 MWth, 148 days/cycle). The iodine element containing I-129 LLFP (without isotope separation) is mixed with YD2 and/or YH2 moderator material to enhance the nuclear transmutation rate. We studied the optimal moderator volume fraction to maximize the transmutation rate (TR, %/year) and the support factor (SF is defined as the ratio of transmuted to produced LLFP). We also investigated the effect of LLFP assembly loading position in the radial blanket and the severe power peak appeared at the fuel assembly adjacent to the LLFP assembly.